Þingeyrar after the Dissolution - Jakob Orri Jónsson (Religions, 2023)
After the Reformation, many monasteries in Scandinavia were provided new purposes or maintained parts of their former functions, serving as everything from hospitals to city halls. In Iceland, however, this did not happen; the monasteries were abandoned, and their functions in society, both ecclesiastical and secular, were, in time, forgotten. This was despite attempts to open schools in some of the former monasteries. While the reasons for the failure of these institutions to transition from being run by ecclesiastical to secular authorities in Iceland remain unknown, the common perception is that these sites remained centers of some influence, power and wealth. This paper will use the monastery site of Þingeyrar, Northern Iceland, as a case study, discussing ceramic data from ongoing excavations there as well as historical data on landholdings to examine the continuity of influence and wealth at monastery sites in Iceland following their dissolution.